Inhibition of Endothelial Notch Signaling Impairs Fatty Acid Transport and Leads to Metabolic and Vascular Remodeling of the Adult Heart. Issue 24 (12th June 2018) - Jabs, Markus; Rose, Adam J.; Lehmann, Lorenz H.; Taylor, Jacqueline; Moll, Iris; Sijmonsma, Tjeerd P.; Herberich, Stefanie E.; Sauer, Sven W.; Poschet, Gernot; Federico, Giuseppina; Mogler, Carolin; Weis, Eva-Maria; et al.
Abstract : Background: Nutrients are transported through endothelial cells before being metabolized in muscle cells. However, little is known about the regulation of endothelial transport processes. Notch signaling is a critical regulator of metabolism and angiogenesis during development. Here, we studied how genetic and pharmacological manipulation of endothelial Notch signaling in adult mice affects endothelial fatty acid transport, cardiac angiogenesis, and heart function. Methods: Endothelial-specific Notch inhibition was achieved by conditional genetic inactivation of Rbp-jκ in adult mice to analyze fatty acid metabolism and heart function. Wild-type mice were treated with neutralizing antibodies against the Notch ligand Delta-like 4. Fatty acid transport was studied in cultured endothelial cells and transgenic mice. Results: Treatment of wild-type mice with Delta-like 4 neutralizing antibodies for 8 weeks impaired fractional shortening and ejection fraction in the majority of mice. Inhibition of Notch signaling specifically in the endothelium of adult mice by genetic ablation of Rbp-jκ caused heart hypertrophy and failure. Impaired heart function was preceded by alterations in fatty acid metabolism and an increase in cardiac blood vessel density. Endothelial Notch signaling controlled the expression of endothelial lipase, Angptl4, CD36, and Fabp4, which are all needed for fatty acid transport across the vessel wall. In endothelial-specific Rbp-jκ–mutant mice, lipase activity and transendothelial transport of long-chain fatty acids to muscle cells were impaired. In turn, lipids accumulated in the plasma and liver. The attenuated supply of cardiomyocytes with long-chain fatty acids was accompanied by higher glucose uptake, increased concentration of glycolysis intermediates, and mTOR-S6K signaling. Treatment with the mTOR inhibitor rapamycin or displacing glucose as cardiac substrate by feeding a ketogenic diet prolonged the survival of endothelial-specific Rbp-jκ–deficient mice. Conclusions: This study identifies Notch signaling as a novel regulator of fatty acid transport across the endothelium and as an essential repressor of angiogenesis in the adult heart. The data imply that the endothelium controls cardiomyocyte metabolism and function. Abstract : Supplemental Digital Content is available in the text.